Economisch belang van de Vlaamse zeehavens: verslag 2003 - Frédéric Lagneaux (National Bank of Belgium, 2005)
– The Flemish maritime ports play a major role in the Belgian economy, not only in terms of the industries they encompass but also as intermodal centres where transhipment activities are concentrated. This update1 paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, through revised results for the period 1997 - 2003. Focusing on the three major variables of value added, employment and investment, it also provides some information about the financial situation of a few vital sectors in each port. A global indication concerning the financial health of the companies studied is also provided, using the NBB bankruptcy prediction model. In addition, it includes figures with respect to the ongoing growth of several cargo traffic segments and provides an overall picture of social developments in the Flemish maritime ports. The indirect effects of these port activities are estimated in terms of value added and employment. Annual account data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects were estimated on the basis of data from the National Accounts Institute. In the Flemish maritime ports, direct VA came to almost 11.5 billion euro and total VA - the sum of direct and indirect VA - to 22 billion euro in 2003. In the same year direct and total employment reached respectively 105,000 and 239,000 full-time equivalents, while direct investment reached 2.5 billion euro. The ongoing developments in the maritime ports sector in the Hamburg - Le Havre range continue to affect the port operations: concentration of capital, privatisation of port logistic services, expansion and dispersion of foreign trade, internationalisation of production and consumption patterns, increase in containerised shipments, etc. Production, trade and transport are no longer considered as individual and isolated activities, but are integrated within a single system, while economies of scale continue. Therefore, ports are becoming real logistic centres: ports able to add value to the goods passing through the port area have a major advantage in a climate of increasing international competition. Flemish ports are following this trend, and that is also reflected in the analysis presented in this report.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments.; Hafen; Branchenentwicklung; Flandern; Wirkungsanalyse